PENGARUH SOSIALISASI PERPAJAKAN, PELAYANAN FISKUS, PENGETAHUAN PAJAK, PERSEPSI PENGETAHUAN KORUPSI, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI ( WPOP ) PADA KPP PRATAMA SENAPELAN PEKANBARU - Veronica, Aldeya; Nurazlina, Nurazlina; Sofyan, Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Tax has an important role in Indonesia, considering the government’s national development requires relatively large funds. The taxation system in Indonesia are depending on how Tax payers are being active on fulfilling the obligation of taxation, the requiring a high compliance. This study aims to examine and analyze the effect taxing socialization, service of tax authorities, tax payer’s knowledge of tax laws, tax perception of corruption, and tax penalties against tax compliance. The population in this study is the individual taxpayers listed on KPP Pratama Pekanbaru Senapelan. The sampling technique using convenience sampling method and determination of sample size in this study was calculated by using the formula of slovin obtained by 100 respondents. The data of this research is using primary data directly through a questionnaire and analyzed using SPSS 20. The data were analyzed to test the hypothesis using multiple linear regression analysis approach. The results of this study show that service of tax authorities, tax payer’s knowledge of tax laws, tax perception of corruption, tax penalties have effect on tax compliance with significant rate 5 % (b2=0,398, b3=0,346, b4=0,233, b5=0,389).. Viceversa taxing socialization has no effect regarding on tax compliance with significant rate 5 % (b1=0,085).Keywords: Socialization, service, knowledge, penalties, compliance